Los factores de productividad que determinan la felicidad laboral (2020)
This degree work presents the reader with a deeper analysis of each of the factors that intervene positively or negatively with regard to job happiness and how it directly or indirectly influences the performance of workers and their effects on the goals group. In addition, a look is given to the way in which the productive factors are related to the happiness or complacency in which the employees who suffer their work activities, as each of these variables are related to each other and how they can affect the methods and productive results of an entire organization.